ANALISIS PROGRAM PRIORITAS PEMERINTAH DESA DALAM MENINGKATKAN KESEJAHTERAAAN MASYARAKAT MELALUI PENGELOLAAN DANA DESA DI DESA MAZIAYA KECAMATAN LOTU KABUPATEN NIAS UTARA - Telaumbanua, Marcthin (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
Social welfare is a state of being fulfilled both physically and spiritually. In Indonesia, to realize social welfare, various social welfare programs have been implemented, including PKH, KUBE, BLT and others. Currently, the government has formed a new program to accelerate the realization of social welfare, namely the village fund program stipulated in Law no. 6 of 2014. With the aim that every village in Indonesia can carry out development independently and can adapt the program to the needs of the village community. One of the beneficiaries of the village fund program is Maziaya Village. Through the management of village funds, priority programs have been implemented in the Maziaya Village area, namely infrastructure development, community empowerment, health, education and BUMDes. The method used in this research is qualitative research with a descriptive approach, data collection techniques are carried out by literature study, observation, interviews and documentation. The results of this study indicate that the priority programs that have been implemented through the management of village funds have had an impact in improving the welfare of the community in Maziaya Village, Lotu District, North Nias Regency.